Akta 123 Akta Siasatan Negara, 1973 & Biro Siasatan Negara Act, 1973 - A, I S (Journal of Malaysian and Comparative Law, 1974)
(1974) 1 (1) JMCL 11 Notes on Legislation Akta 123 Akta Siasatan Negara, 1973 & Biro Siasatan Negara Act, 1973 - I.S.A.